Structure gradients by microfocus synchrotron X-ray diffraction in shell-core polyamide microcapsules - Denchev, Z. (2015)
Polyamide microcapsules are of demand in many industries e.g., compression- and rotational molding, selective laser sintering, cosmetics etc. In bioengineering, polyamide-microcapsules can be attractive carriers for protein or enzyme immobilization. The distribution of the solid filler in microcapsules is a function of the manufacturing conditions and is often of decisive importance for certain applications. Such measurements are not possible by means of conventional X-ray techniques or electron microscopy due to the large size of the X-ray beam and sample preparation difficulties, respectively. This work reports on the measurements of the structure- and composition gradients in novel microcapsules with polyamide 6 (PA6) porous shells and diameters in the 25-50 μm range obtained by emulsion anionic polymerization. The microcapsules were loaded in situ with various amounts and types of inorganic, finely dispersed materials: nanoclays, carbon allotropes, and metal particles. Thin layers of the respective microcapsule samples were scanned along two perpendicular axes with a 5x5 μm synchrotron beam in WAXS mode covering areas of 3025 μm2. The microfocos WAXS results obtained showed irregular distribution of the filler within the PA6 microcapsules causing changes in the content of α- and γ-PA6 polymorphs in shell sections of 25 μm2 each. Similar measurements were performed with composite plates obtained by compression molding of certain amounts of the respective microcapsules. These unique WAXS studies helped characterize the core nanostructure of the loaded PA6 microcapsules and how it transits into the molded part. In such a way a direct relation was made between the reaction parameters of the microcapsule-forming polymerization process and the nanostructure of the molded samples.